Dose-dependent effects of mTOR inhibition on weight and mitochondrial disease in mice - Johnson, Simon C.; Yanos, Melana; Sangesland, Maya; Bitto, Alessandro; Castanza, Anthony; Gagnidze, Arni; Cordoba, Jose; Gonzalez, Brenda; Gupta, Kanav; Hui, Jessica; Jarvie, Conner; Johnson, Brittany; et al. (Frontiers in Genetics, 2015)
Rapamycin extends lifespan and attenuates age-related pathologies in mice when administered through diet at 14 parts per million (PPM). Recently, we reported that daily intraperitoneal injection of rapamycin at 8 mg/kg attenuates mitochondrial disease symptoms and progression in the Ndufs4 knockout mouse model of Leigh Syndrome. Although rapamycin is a widely used pharmaceutical agent dosage has not been rigorously examined and no dose-response profile has been established. Given these observations we sought to determine if increased doses of oral rapamycin would result in more robust impact on mTOR driven parameters. To test this hypothesis, we compared the effects of dietary rapamycin at doses ranging from 14 to 378 PPM on growth in control and Ndufs4 knockout mice and on health and survival in the Ndufs4 knockout model. High dose rapamycin was well tolerated, dramatically reduced growth, and overcame gender differences. The highest oral dose, approximately 27-times the dose shown to extend murine lifespan, increased survival in Ndufs4 knockout mice similarly to daily rapamycin injection without observable adverse effects. These findings have broad implications for the effective use of rapamycin in murine studies and for the translational potential of rapamycin in the treatment of mitochondrial disease. This data, further supported by a comparison of available literature, suggests that 14 PPM dietary rapamycin is a sub-optimal dose for targeting mTOR systemically in mice. Our findings suggest that the role of mTOR in mammalian biology may be broadly underestimated when determined through treatment with rapamycin at commonly used doses.